Forms Distribution of Heavy Metals and Their Ecological Risk Evaluation in Soils of Ion Adsorption Type in the Rare Earth Mining Area of Southern Jiangxi, China - ZHANG Sai; YU Yang; WANG Deng-hong; WANG Wei; ZHANG Hong-guo; CEN Kuang (Yankuang ceshi, 2020)
OBJECTIVES The open-pit mining of rare earth mines easily causes heavy metal pollution problems. Studies have shown that the soil of the rare earth mining area in southern Jiangxi has been polluted by heavy metals of Cd and Pb in low and moderate degrees. Environmental quality assessment usually uses pollution factors (total heavy metal content) as indicators of the degree of pollution, which can only reflect the degree of enrichment of heavy metals. OBJECTIVES To investigate the forms of heavy metals in the soil of the rare earth mining area in southern Jiangxi Province, migration ability and bioavailability. METHODS Based on the forms analysis of soil heavy metals measured by inductively coupled plasma-mass spectrometry (ICP-MS), the ecological risk of soil heavy metals in the rare earth mining area was evaluated using the geoaccumulation index method, potential ecological hazard index method and RAC risk assessment. RESULTS The heavy metals in the soil in the study area mainly existed in the residual form, accounting for 65.5% of the total. The average content of Cd and Pb in the soil samples was 1.72 times and 2.14 times the soil background value of Jiangxi Province, respectively. The average value of Cd in the soil in the farmland along the river downstream of the mine and the average value of Pb in the farmland near the tailing pond were 2.33 times and 3.06 times background value, respectively. The Cd or Pb content of the 22.7% samples exceeded the risk screening value. Among them, the exchangeable form of Cd and Pb accounted for 47.1% and 13.5% of the total amount, respectively, secondary to the residual form. Geoaccumulation index and potential ecological risk assessment results show that the accumulation degree and ecological risk level of Cd and Pb were higher, and Co, Ni, Cu, and Zn were lower. RAC risk assessment results show that Cd ecological risk was higher, whereas Co, Zn, and Pb was medium and Cu and Ni was low. Although the focal point and some results of the three evaluation methods were also different, the comprehensive conclusion showed that the soil Cd pollution and migration activities in the mining area were high, and the ecological risk was high. Conclusion The research results provide scientific basis for identifying the potential environmental risks of farmland soil in rare earth mining areas and propose effective prevention, emergency response and mitigation procedures.